Chemical , Physical and Microbiological Characteristics of Etawa Crossbred Goat Milk In Bogor - Ratya, N.; Taufik, E.; Arief, I. I. (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2017)
Goat milk quality is an important aspect for consumers. Information about the quality of local goat milk, such as Etawa crosbreed, is still rare. Therefore it is necessary to investigate this information especially in Bogor area. The aim of this research was to analyze chemical, physical and microbiological quality of etawa crossbred goat milk in Bogor. Milk samples were collected from three dairy goat farms in Bogor. Data were analyzed by using Krusskal Wallis one way ANOVA and Mann-Whitney U tests. The observed variables werecontents of fat, solid non fat (SNF), protein, lactose, milk’s density, pH, number of coliform and total plate count (TPC). The results showed that there were significant differences in density value and coliform number among milks of three farms. The quality of etawa crossbred goat milk includes fat, protein, lactose contents, pH, total microbes of three farms in Bogor was categorized in premium quality according to Thai Agriculture Standard (TAS) No 6006-2008. SNF values of the three farms, milk density value at farm two and pH value at farm three were catogorized under the standard set by TAS No 6006 (2008).